2015
DOI: 10.1371/journal.pone.0120217
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor C-Myc Suppresses MiR-23b and MiR-27b Transcription during Fetal Distress and Increases the Sensitivity of Neurons to Hypoxia-Induced Apoptosis

Abstract: Previous studies reported that the expression of miR-23b-27b cluster was downregulated in embryonic brain cortices during hypoxia-induced neuronal apoptosis. However, the mechanism underlying this downregulation is not completely understood. Here, we report that the transcription factor c-Myc plays an important role in regulating the expression of miR-23b-27b cluster during hypoxia. First, the c-Myc protein level was significantly elevated in embryonic brain cortices in a mouse model of fetal distress. Second,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
0
11
1
Order By: Relevance
“…A positive feedback mechanism mediated by p53-miR-24-MDM2 activates miR-23b cluster and miR-125a-5p expression, whereas, a NF-kB p65-mediated negative regulatory loop blocks the transcriptional activation of both miR-23b cluster and miR-125a-5p. Importantly, previous studies have reported that AP-1 and c-Myc are also able to suppress the expression of miR-23b cluster, confirming they act as “bona fide” tumor suppressor microRNAs 41 , 42 . EMT is a multistep process associated with metastasis and drug resistance.…”
Section: Discussionmentioning
confidence: 65%
“…A positive feedback mechanism mediated by p53-miR-24-MDM2 activates miR-23b cluster and miR-125a-5p expression, whereas, a NF-kB p65-mediated negative regulatory loop blocks the transcriptional activation of both miR-23b cluster and miR-125a-5p. Importantly, previous studies have reported that AP-1 and c-Myc are also able to suppress the expression of miR-23b cluster, confirming they act as “bona fide” tumor suppressor microRNAs 41 , 42 . EMT is a multistep process associated with metastasis and drug resistance.…”
Section: Discussionmentioning
confidence: 65%
“…Several studies have demonstrated that miR-27b plays an important role in regulating various physical and pathological process by repressing distinct targets, such as KH-type splicing regulatory protein (38) and apoptotic protease activating factor-1 (Apaf-1) (39). Most of these miR-27b targets modulate inflammatory response and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miR-23b expression was inversely correlated with DLX1 expression, suggesting that miR-23b may be able to downregulate DLX1 expression via posttranscriptional repression (Figure 3d). The exact function of the miR-23b-27b cluster has yet to be fully uncovered, but it has been shown to confer neuroprotective effects both in vitro and in vivo, via direct repression of apoptotic protease activating factor-1 (APAF1) specifically in neurons (Chen et al, 2014(Chen et al, , 2015Sun et al, 2018). However, in the current study, we did not find significant differences in APAF1 expression in alcohol-treated neurons (p > 0.05; FDR = 0.932), suggesting that additional miR-23b-independent mechanisms could be regulating APAF1 expression.…”
Section: Alcohol Exposure Alters Transcripts Associated With Both Gabaergic and Glutamatergic Neuron Differentiationmentioning
confidence: 99%